Acceptance of aging among Japanese adults aged 20–89 - Miho Nakajima; Hikari Kinjo (Cogent Psychology)
Objectives Acceptance of awareness of age-related change (AARC) is vital for mental health, yet the mechanisms underlying this process remain unclear. This study examined the relationships among AARC, subjective emotional valence toward AARC, and age acceptance.Methods and Measures A cross-sectional survey was conducted with 2896 Japanese adults aged 20–89. Participants completed a questionnaire assessing the following variables: AARC, emotional evaluation of AARC, and aging acceptance.Results Logistic regression indicated that a positive evaluation of AARC was associated with greater acceptance of physical and psychosocial aging. Generalized linear modeling and chi-square tests showed that ‘Muscular/joint changes and appearance’ were types of AARC negatively evaluated and challenging to accept, whereas ‘Illness/injury’ was also negatively evaluated but easier to accept. For psychosocial AARC, ‘Psychological decline’ was negatively evaluated and hard to accept, while ‘Maturation’ was positively evaluated and easier to accept.Conclusion Strategies for age acceptance may vary by domain. Minimizing focus on negative physical changes supports physical age acceptance, while emphasizing personal growth fosters psychosocial acceptance.